Contributing factors toward social problems among adolescents in governmental rehabilitation center in Kuala Lumpur - Lim, Y. J.; A. R., Nur Amirah; Minhat, Halimatus Sakdiah; Hamedon, Titi Rahmawati (Community Health Society Malaysia, 2014)
Background: Adolescents are often associated with a variety of behavioural and social problems as a result of prominent high-risk behaviour among this age group. The aim of this study is to determine the contributing factors toward social problems among adolescents admitted to the governmental rehabilitation centres in Kuala Lumpur. Methods: A cross-sectional study was conducted among 146 adolescents, randomly selected from 3 governmental rehabilitation centres in Kuala Lumpur under the supervision of the Department of Social Welfare namely, Asrama Sentosa, Asrama Bahagia and Sekolah Tunas Bakti Sg Besi. A pre-tested guided self-administered questionnaire was used for data collection, involving the socio-demographic information, social problems and perceived social support from family members, peer’s influence and environmental factors. The Cronbach’s alpha values obtained for the different sections of the questionnaire was ranging between 0.6 and 0.7. Results: The results showed majority of the adolescents involved had a mean age of 16 years old (IQR 2), male (78%), Malay (89.7%) and received secondary education level (84.9%). Most of their parents were still married (66.4%), received at least secondary education (47.3%) and total household income of between RM760 and RM1500 (38.4%). Most common social problems reported were violence (23.3%), illicit drug taking (18.5%) and thievery (15.1%), with teenage pregnancy the least common (1.4%). Environmental factors was found to be the only significant factor associated with the social problems committed by the adolescents (X2 = 4.463, p<0.05). Conclusion: This findings suggest the importance of developing a more conducive and healthy environment for the adolescents in order to tackle the increasing social problems among the adolescents.